2020
DOI: 10.1123/jcsp.2018-0081
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Training to Promote Psychological Flexibility in Ice Hockey Performance: A Controlled Group Feasibility Study

Abstract: Despite the growing popularity of mindfulness and acceptance-based performance enhancement methods in applied sport psychology, evidence for their efficacy is scarce. The purpose of the current study is to test the feasibility and effect of a psychological training program based on Acceptance and Commitment Training (ACT) developed for ice hockey players. A controlled group feasibility designed study was conducted and included 21 elite male ice hockey players. The ACT program consisted of four, once a week, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 23 publications
0
24
0
4
Order By: Relevance
“…This increases the probability of improving performance (Josefsson et al, 2019 ). Earlier studies, including MAC interventions, have demonstrated increased psychological flexibility and improved sport performance (Gross et al, 2018 ; Lundgren et al, 2019 ). Research in occupational settings has found similar results, indicating that acceptance-predicted mental health and an objective measure of performance including the beneficial effects of having more job control were enhanced when people had higher levels of acceptance (Bond and Bunce, 2003 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This increases the probability of improving performance (Josefsson et al, 2019 ). Earlier studies, including MAC interventions, have demonstrated increased psychological flexibility and improved sport performance (Gross et al, 2018 ; Lundgren et al, 2019 ). Research in occupational settings has found similar results, indicating that acceptance-predicted mental health and an objective measure of performance including the beneficial effects of having more job control were enhanced when people had higher levels of acceptance (Bond and Bunce, 2003 ).…”
Section: Discussionmentioning
confidence: 98%
“…Due to the heterogeneous sample of athletes from a range of different sports, the Borg CR100 scale was chosen as the optimal way to measure performance. Based on earlier research and theoretical assumptions (Gardner and Moore, 2004 ; Bond et al, 2013 ; Gross et al, 2018 ; Lundgren et al, 2019 ), we expected the PFSS to be negatively related to performance.…”
Section: Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the ACT approach in ice hockey is to develop psychologically flexible ice hockey players (Lundgren et al, 2020). A psychologically flexible player approaches their ice hockey development and game being open and aware of their athletic experience no matter the content of the private events or obstacles they may encounter.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent controlled group study, ACT was adapted to the ice hockey context to function as a performance enhancement program for elite ice hockey players (Lundgren et al, 2020). The study sample consisted of 21 players in total.…”
Section: Introductionmentioning
confidence: 99%